Legal Approach towards Social Health Security Agencies from The Perspective of Social Insurance as a Health Service - Mucahrom, Rully Syahrul; Muin, Fatkhul (Universitas Pahlawan Tuanku Tambusai, 2025)
The state's responsibility for efforts to create a good health service system in order to provide welfare to the community. The social security law has placed a model of protection for the community with a legal approach through social insurance with the basic principle of mutual cooperation. In January 2023, the government spent around IDR 5.3 trillion to protect public health, an increase of 12% compared to last year (2022), making the Health Social Security Administering Agency abbreviated as BPJS Kesehatan as the manager of social insurance for medical assistance need to continue to develop to meet needs. The health insurance scheme managed by the state with the provision of health equipment as an effort to fulfill the state's constitutional responsibility. This study analyzes the state's responsibility in providing health insurance for the community as an effort to fulfill citizens' rights through a legal approach.